An unprecedented constraint on water content in the sunlit lunar exosphere seen by Lunar-based Ultraviolet Telescope of Chang׳e-3 mission. (May 2015) - Wang, J.; Wu, C.; Qiu, Y.L.; Meng, X.M.; Cai, H.B.; Cao, L.; Deng, J.S.; Han, X.H.; Wei, J.Y.
Abstract: The content of OH/H2 O molecules in the tenuous exosphere of the Moon is still an open issue at present. We here report an unprecedented upper limit of the content of the OH radicals, which is obtained from the in situ measurements carried out by the Lunar-based Ultraviolet Telescope, a payload of Chinese Chang׳e-3 mission. By analyzing the diffuse background in the images taken by the telescope, the column density and surface concentration of the OH radicals are inferred to be < 10 11 cm − 2 and < 10 4 cm − 3 (by assuming a hydrostatic equilibrium with a scale height of 100 km), respectively, by assuming that the recorded background is fully contributed by their resonance fluorescence emission. The resulted concentration is lower than the previously reported value by about two orders of magnitude, and is close to the prediction of the sputtering model. In addition, the same measurements and method allow us to derive a surface concentration of < 10 2 cm − 3 for the neutral magnesium, which is lower than the previously reported upper limit by about two orders of magnitude. These results are the best known of the OH (MgI) content in the lunar exosphere to date. Abstract : Highlights: We study the lunar exosphere by the in situ measurements via optical techniques. The content of the exosphere is derived by analyzing the sky background seen on the Moon. An unprecedented upper limit of the concentration is inferred for the OH radicals and MgI.